Effect of Core Self-Evaluation and Career Competencies on Employee Well-Being in the New Normal Era: Efek Evaluasi Diri Inti dan Kompetensi Karir pada Kesejahteraan Karyawan di Era Kenormalan Baru - Wardani, Laila Meilyandrie Indah; Nurlita, Ratna Sari; Sombuling, Agnis (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2023)
Employee well-being is a crucial aspect for companies, as it enables employees to perform optimally and make their most significant contributions. Therefore, this study aimed to investigate the effect of core self-evaluation and career competencies on employee well-being in the new normal era. The sample population consisted of 366 employees in the Greater Jakarta area from several industrial sectors, such as trade, services, education, military, civil service, and telecommunications. The results showed that core self-evaluation and career competencies had a simultaneous effect on employee well-being in the new normal era. The dimension of self-esteem within core self evaluation variable had the highest influence on employee well-being, particularly the psychological well-being dimension. The findings of this study were expected to provide insight to employees and agencies regarding the importance of self-evaluation in maximizing the competencies of employees and achieving prosperity in the workplace, social environment, and daily life.